(untitled) (مجلة دراسات إقلیمیة, 2026)
Research Idea: Transitional justice in Iraq is conceptualized as a mechanism for managing collective memory in relation to past human rights violations and repression. While compensatory justice has been implemented to redress victims, significant weaknesses remain in approaches to memory management. As a result, Iraq faces challenges in establishing a shared national memory that can underpin national identity beyond social and political divisions. Objective: This study examines the Iraqi context through transitional justice and explores its role in constructing collective memory aimed at addressing the legacy of conflict and human rights violations. Methodology: The study adopts an analytical approach supported by historical and descriptive methods to examine events and relevant concepts. Results: The findings indicate that transitional justice in Iraq should serve as a foundation for building national identity. This requires strengthening the rule of law, implementing education programs that respect cultural diversity, and promoting acceptance of the other. Conclusion: The study concludes that building a collective national memory in Iraq depends on reinforcing the authority of law as the main mechanism for dispute resolution and preventing individual retaliation, thereby eliminating the impulses. of revenge.